The Effect of Laughter Therapy for Depression Level among Geriatric Patients at Pangesti Lawang Nursing Home - Susmini; Wahyu Dwi Ari WIbowo; Sapondra Wijaya; Nindya Amelia (International Journal of Nursing and Health Services (IJNHS), 2021)
Background: The elderly will experience decreased organ function and social changes experienced. 1 in 5 elderly suffers from mental or neurological disorders. Depression is underdiagnosed and undertreated in primary care settings because they appear together with other elderly problems. Depression in the elderly can reduce the quality of life and increases the risk of suicide. As a non-pharmacological alternative treatment, laughter and classical music therapy positively affect mental health, especially depression. Methods: The Design of this study is a quasi-experimental research with pre and post-test control group design. Data were collected with a short-form GDS questionnaire 15 Statements. Results: A total of 32 participants were from the elderly at the PangestiLawang Nursing Home. Laughter Therapy showed a significant GDS score before and after being given therapy p-value = 0.000. Classical Music Therapy also showed a significant GDS score before and after given therapy p-value = 0.002. In the comparison between both therapies, there was no significant difference between the treatment p-value = 0.541. Conclusion: There was a difference GDS before and after the elderly were given laughter therapy and classical music therapy, but there was no significant difference in GDS score between laughter therapy and classical music therapy, Both of them were given the same effect on decreasing GDS Score for the Elderly at PangestiLawang Nursing Home